2017
DOI: 10.1590/0100-29452017574
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY OF ACEROLA (Malpighia emarginata) TREATED WITH GIBBERELIC ACID AND STORED UNDER REFRIGERATION

Abstract: ABSTRACT-The goal of this study was study the postharvest quality of acerola clone BRS 236 (Malpighia emarginata D.C.) which was harvested at physiological maturity and submitted to four treatments under immersion during 5 minutes at 25 °C, which are: control (water), 60 mg L . After treatment the fruits were packed in polystyrene trays and placed with polyethylene film and then stored at 10 ± 2 °C and 85 ± 5% RH for 12 days. Were analyzed in three days intervals (0, 3, 6, 9 and 12 days): skin color, firmness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
3
0
4
Order By: Relevance
“…Apparently, gibberellin affects the anthocyanin content in the fruit, depending on the applied amount (Souza et al 2017). Rosso & Mercadante (2007) affirm that anthocyanins may condense with vitamin C and promote an accelerated degradation of these compounds.…”
Section: Resultsmentioning
confidence: 95%
“…Apparently, gibberellin affects the anthocyanin content in the fruit, depending on the applied amount (Souza et al 2017). Rosso & Mercadante (2007) affirm that anthocyanins may condense with vitamin C and promote an accelerated degradation of these compounds.…”
Section: Resultsmentioning
confidence: 95%
“…Acerola is a very fragile and perishable fruit mainly due to the accelerated loss of esh rmness during ripening (Carrington and King, 2002;Quoc et al, 2015;Souza et al, 2017), which has been reported to be associated with increasing activity of cell wall degrading enzymes and loss of cellular turgor pressure (Santos et al, 2019). Indeed, ripe acerolas have lower esh rmness, compared to other fruit species (Batista et al, 2015), making the fruit more susceptible to mechanical damage and losses.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype PROG 069 ranked fourth in both growing seasons, according to the selection index. One of the most important quality traits observed in the genotype PROG 069 was the high fruit esh rmness, which increases resistance to mechanical damage and postharvest live of the fruit (Quoc et al, 2015;Souza et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…SegundoCarpentieri-pipolo et al (2000) frutos grandes que possuem um maior diâmetro geralmente são os que apresentam uma maior quantidade de polpa sendo esse um fator favorável a seleção. No estudoSouza et al (2017) destacaram características importantes consideradas determinantes na qualidade pós colheita das acerolas, como a cor que está diretamente associado a concentração de pigmentos que na acerola tem predominância as antocianinas. Outro parâmetro físico importante é a firmeza, que está relacionado com estrutura das paredes celulares e sua integridade, ressaltando que frutos com alta firmeza possui uma vida útil pós colheita mais prolongada.…”
unclassified